The Making of a Manager: Evidence from Military Officer Training - Grönqvist, Erik; Lindqvist, Erik (Journal of Labor Economics, 2016)
We show that officer training during the Swedish military service has a strong positive effect on the probability of attaining a managerial position later in life. The most intense type of officer training increases the probability of becoming a civilian manager by about 5 percentage points, or 75%. Officer training also increases educational attainment post–military service. We argue that the effect on civilian leadership could be due to the acquisition of leadership-specific skills during the military service, and we present suggestive evidence related to alternative mechanisms, such as signaling, networks, and training unrelated to leadership.